ANALISIS KRITIS VALIDASI DAN EVALUASI INFORMASI DIGITAL - M. Tamrin Junaidi, Nadia Zakiatul Mutiah; Jamal Jabarpaj, Salwa Az- Zahra, Eva Iryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In the digital age characterized by the rapid and abundant flow of information, the ability to validate and evaluate information has become very important. Digital information validation is a process that aims to ensure the authenticity and veracity of data obtained from various online sources. It involves verifying information to prevent the spread of fake news and misleading information. On the other hand, information evaluation involves assessing the quality, objectivity and purpose of information, which is crucial for informed decision-making. This article discusses the importance of both processes in the context of accurate decision-making, the challenges people face in filtering information, and strategies that can be implemented to improve individuals' ability to select accurate and trustworthy information. By doing so, it is hoped that people can become responsible users of digital information, able to filter information wisely, and contribute to a healthier and more informative information environment.